A review of dropwise condensation: Theory, modeling, experiments, and applications. (October 2020) - El Fil, Bachir; Kini, Girish; Garimella, Srinivas
Highlights: Progress in understanding of dropwise condensation (DWC) reviewed. Modeling and experimental studies in external and internal DWC considered. Applications for DWC explored and potential impact assessed. Need for accurate heat transfer measurements and improved modeling highlighted. Promoting durable DWC under industrial conditions remains a challenge. Abstract: Dropwise condensation (DWC) is a heterogeneous phase-change process where vapor changes to liquid in the form of discrete drops on an unwetted surface. The heat transfer coefficients associated with DWC are significantly higher than those of filmwise condensation (FWC) αDWC   ≫  αFWC . Therefore, there is considerable interest in DWC, which could have prospects for a variety of industrial applications such as thermal power and process plants, space-conditioning and refrigeration, electronics cooling, and others. However, there have been discrepancies between the results from different researchers in this field. It was only in the late 1960s that dropwise condensation mechanism and theory started becoming formalized. This paper presents focuses on the literature on the theory, underlying mechanisms, experiments and applications of dropwise condensation. Insights gained from this review and assessment are also used to identify the need for accurate heat transfer measurements and improved modeling of DWC.